The transitivity of folklore: A comparison study of Indonesian and English folklore - Eline Rozaliya Winarto (Concept : Community Concern for English Pedagogy and Teaching, 2018)
Folklore has moral value that is meaningful. Moreover, systemic functional linguistics has three lines of meaning to analyse the transitivity of a clause. In this research, the writer tries to figure out the transitivity of folklore, Indonesian and English folklore. This descriptive analysis has 74 clauses for Indonesian folklore and 45 clauses for English folklore. Having analysed the data, the writer found that material process is the most process appeared in both Indonesian and English folklores. Meanwhile, the transitivity’s of Indonesian folklore are material, mental, verbal, relational, and existential. Furthermore, the transitivity’s of English folklore are material, mental, verbal, relational and behavioural. Keywords: transitivity, Indonesian folklore, English folklore.